Hydromorphologic Control of Streambed Fine Particle Standing Stocks Influences In-stream Aerobic Respiration - Meredith, Warren; Drummond, Jennifer; Bernal, Susana; Tobella, Marta; Ribot, Miquel; Schumer, Rina; Sabater, Francesc; Martí, Eugènia (Frontiers in Water, 2021)
Fine particulate organic matter (FPOM) accumulated in the streambed is a major component of organic matter budgets in headwater streams and greatly affects productivity and metabolism of stream communities. The spatiotemporal distribution of benthic FPOM in the stream, as well as its quantity and quality, depend on the inputs from different source types (natural or anthropogenic) in the catchment, such as the riparian vegetation or effluents from wastewater treatment plants. In addition, stream flow is a key driver of FPOM dynamics, which influences the balance between its transport and accumulation in the streambed. Yet, the link between FPOM dynamics and its effects on stream metabolism is still largely unknown. The aim of this study was to investigate the influence of stream channel hydromorphology on water transport and the accumulation of fine particulate matter (FPM) in the streambed and its quality. In addition, we quantified the metabolic activity associated with FPOM, and its potential contribution to whole-reach ecosystem respiration. The study was conducted in three reaches that were modified to change their hydromorphological characteristics . The reaches were located downstream of a wastewater treatment plant effluent in the Cànoves stream (Catalonia, NE Spain). Within each reach, we measured variability in streambed FPM standing stocks at the habitat-scale and characterized its quality based on organic matter, carbon and nitrogen content. We also measured the microbial metabolic activity associated with the FPM using the resazurin-resorufin bioreactive tracer as a proxy for aerobic respiration. At reach-scale, we characterized water transport and metabolic activity with combined additions of hydrological and bioreactive tracers. At the habitat-scale, water velocity determined streambed accumulation of FPM, and microbial metabolic activity increased with the proportion of organic matter in FPM, indicating the bioactive capacity of FPM. Results demonstrate that the interplay of hydrologic exchange and residence time in streambed sediments associated with the microbial metabolic activity of benthic FPOM can ultimately influence reach-scale metabolic activity. These results can have important implications within the context of stream restoration since induced hydromorphological changes can alter the stream’s metabolic activity; and ultimately the in-stream capacity to attenuate organic matter and nutrient loads.